Does the Use of Intravenous Immunoglobulin Improve Clinical Outcomes in Adults With Autoimmune Encephalitis? A Systematic Review - Anahat Kalra; Olivia Mackay; Emma Thomas‐Jones; Tom Solomon; Paula Foscarini‐Craggs (Brain and Behavior)
ABSTRACT Background Autoimmune encephalitis is an immune‐mediated inflammatory condition affecting the central nervous system. Current best‐practice guidelines recommend intravenous immunoglobulin (IVIG) for use if corticosteroids are ineffective, but the evidence surrounding the efficacy of IVIG in autoimmune encephalitis is yet to be evaluated. Objectives Perform a systematic review of the available literature to evaluate the efficacy of IVIG in autoimmune encephalitis and the impact of IVIG on clinical outcomes. Methods This systematic review was written following PRISMA‐S guidelines. Papers eligible for inclusion were primary research including adults aged 16 years and above, with a suspected or confirmed diagnosis of autoimmune encephalitis, treated using IVIG. Each included study was assessed for quality. Results and conclusion From 2533 records, 27 studies met the inclusion criteria. The use of IVIG is associated with improved short‐term and long‐term neurological outcomes. There is evidence that IVIG may be more effective when used in combination with corticosteroids. The use of IVIG is significantly associated with reduced seizure incidence in patients. Where recorded, adverse effects related to IVIG were few. There is insufficient data available on how IVIG impacts mortality rates, discharge rates, and its effects according to different types of autoimmune encephalitis. Out of the included papers, there was 1 randomized controlled trial (RCT), 3 nonrandomized trials and 23 cohort studies. 25 of 27 papers were deemed to have a high or serious risk of bias. Heterogeneous study design and the quality of studies were major limiting factors for this review, highlighting the need for further research.